Self-Compassion and Grit in the Context of Social Judgment - Lauren Hytman; Nancy L. Kocovski (SAGE Open, 2023)
Self-compassion and grit are each positively associated with adaptive characteristics, and negatively associated with psychological distress. Limited research exists on the relationship between grit and self-compassion, and there is a paucity of research on the impact of grit on social anxiety. Undergraduate participants ( N  = 184) completed online measures of grit, self-compassion, well-being, and psychological distress. They also recalled a recent social situation in which they felt judged and reported state levels of self-compassion. As hypothesized, grit (specifically the perseverance subscale) was related to greater state self-compassion regarding the social judgment situation participants recalled. Further, there was support for self-compassion as a mediator of the relationship between grit and state anxiety. However, how self-compassionate participants reported being in their social stressor was best predicted by trait self-compassion and state anxiety. Finally, the type of social judgment situation mattered: participants were less self-compassionate when they recalled performance situations compared to social interaction situations. Findings suggest continued research on how grit and self-compassion may influence one another over time in the context of social judgment.